Reliability of Buildings and Structures: General Requirements, Terms, and Indicators - Klimov, Mykhailo; Valovoi, Oleksandr; Valovoi, Maksym (Academic journal Industrial Machine Building Civil Engineering, 2025)
Modern buildings and structures, with their increasing complexity in design and operation, are transforming into unique engineering systems, the failure of which can lead to significant material, moral, and human losses. Ensuring their reliability is one of the most critical problems in the modern construction industry. This article systematizes the key provisions of reliability theory as applied to construction objects. The main terms, such as dependability (failure-free operation), durability, maintainability, and storability, are considered, and quantitative reliability indicators are analyzed. The evolution of calculation methods is investigated, charting the transition from outdated deterministic approaches (the allowable stress method) to modern probabilistic methodologies, which are based on the concept of limit states. The dynamics of reliability over the object’s life cycle are discussed, highlighting the typical "bathtub curve" phases of burn-in, normal operation, and wear-out. The article identifies the key challenges in the practical application of modern probabilistic methods, particularly the gap between advanced theoretical models and the lack of systematized empirical data on failures, which is necessary for the accurate calibration of national standards.